C-type natriuretic peptide inhibits leukocyte recruitment and platelet-leukocyte interactions via suppression of P-selectin expression - Scotland, Ramona S. (National Academy of Sciences, 2005)
The multifaceted process of immune cell recruitment to sites of tissue injury is key to the development of an inflammatory response and involved in the pathogenesis of numerous cardiovascular disorders. We recently identified C-type natriuretic peptide (CNP) as an important endothelium-derived mediator that regulates vascular tone and protects against myocardial ischemia/reperfusion injury. Herein, we investigated whether CNP inhibits leukocyte recruitment and platelet aggregation and thereby exerts a potential antiinflammatory influence on the blood vessel wall. We assessed the effects of CNP on leukocyte-endothelial cell interactions in mouse mesenteric postcapillary venules in vivo in animals with high basal leukocyte activation (endothelial nitric oxide synthase knockout mice, eNOS(-/-)) or under acute inflammatory conditions (induced by interleukin-1β or histamine). CNP suppressed basal leukocyte rolling in eNOS(-/-) mice in a rapid, reversible, and concentration-dependent manner. These effects of CNP were mimicked by the selective natriuretic peptide receptor-C agonist cANF(4-23). CNP also suppressed leukocyte rolling induced by IL-1β or histamine, inhibited platelet-leukocyte interactions, and prevented thrombin-induced platelet aggregation of human blood. Furthermore, analysis of human umbilical vein endothelial cells, leukocytes, and platelets revealed that CNP selectively attenuates expression of P-selectin. Thus, CNP is a modulator of acute inflammation in the blood vessel wall characterized by leukocyte and platelet activation. These antiinflammatory effects appear to be mediated, at least in part, via suppression of P-selectin expression. These observations suggest that endothelial CNP might maintain an anti-atherogenic influence on the blood vessel wall and represent a target for therapeutic intervention in inflammatory cardiovascular disorders.